α‐Emitting cancer therapy using (211)At‐AAMT targeting LAT1 - Kaneda‐Nakashima, Kazuko (Cancer Sci, 2021)
α‐Methyl‐l‐tyrosine (AMT) has a high affinity for the cancer‐specific l‐type amino acid transporter 1 (LAT1). Therefore, we established an anti‐cancer therapy, with (211)At‐labeled α‐methyl‐l‐tyrosine ((211)At‐AAMT) as a carrier of (211)At into tumors. (211)At‐AAMT had high affinity for LAT1, inhibited tumor cell growth, and induced DNA double‐stranded breaks in vitro. We evaluated the accumulation of (211)At‐AAMT in vivo and the role of LAT1. Treatment with 0.4 MBq/mouse (211)At‐AAMT inhibited tumor growth in the PANC‐1 tumor model and 1 MBq/mouse (211)At‐AAMT inhibited metastasis in the lung of the B16F10 metastasis model. Our results suggested that (211)At would be useful for anti‐cancer therapy and that LAT1 is suitable as a target for radionuclide therapy.